Application of CRISPR/Cas9 technology to improve the important traits in coffee. Issue 1 (January 2022) - Santoso, T J; Sisharmini, A; Syafaruddin,
Abstract: Coffee is an essential estate crop that has a tremendous economic impact globally and is cultivated in many countries worldwide. However, due to the long process, the genetic improvement of coffee to develop new varieties through conventional breeding is slow and difficult. In addition, its production is constrained mainly by biotic and abiotic stresses. Therefore, developing superior coffee varieties with tolerance to abiotic and biotic stresses and improved quality is vital. The invention of genome editing technology has evolved the technologies in agriculture. CRISPR/Cas9 technology is a genome editing technique that more commonly applied for its simplicity, robustness, and high efficiency, compared to other techniques such as ZFN a nd TALEN. Furthermore, to develop new superior va rieties of coffee, the CRISPR/Cas9 system provides an opportunity to improve by adding desirable traits or removing unwanted characteristics. Therefore, genome editing techniques in coffee breeding can help to increase yield, resistant/tolerant of biotic a nd abiotic, reduce input costs, a nd improve product quality. This article discusses the latest innovations of the CRISPR/Cas9 technique applicable in agriculture and prospectively on genome editing to improve important characters in coffee.